2021
DOI: 10.1111/bdi.13133
|View full text |Cite
|
Sign up to set email alerts
|

The effect of prenatal lithium exposure on the neuropsychological development of the child

Abstract: Objectives Lithium is an effective treatment for bipolar disorder, also during pregnancy to prevent the recurrence of episodes in the perinatal period. Little is known about the neuropsychological development of lithium‐exposed offspring. The current study was designed to investigate neuropsychological functioning in lithium‐exposed children with the aim to provide further knowledge on the long‐term effects of lithium use during pregnancy. Methods Participants were offspring of women with a diagnosis of bipola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Available data were reassuring, although limited, and suggest that lithium use during pregnancy is associated with normal child neurodevelopment. This observation is in line with a very recent study founding no evidence for significantly altered neuropsychological functioning of lithium-exposed children at the age of 6–14 years (Poels et al 2022 ). Specifically, authors found no association between prenatal lithium exposure and IQ and no relationship between lithium blood level during pregnancy and neuropsychological functioning (Poels et al 2022 ).…”
Section: Discussionsupporting
confidence: 92%
“…Available data were reassuring, although limited, and suggest that lithium use during pregnancy is associated with normal child neurodevelopment. This observation is in line with a very recent study founding no evidence for significantly altered neuropsychological functioning of lithium-exposed children at the age of 6–14 years (Poels et al 2022 ). Specifically, authors found no association between prenatal lithium exposure and IQ and no relationship between lithium blood level during pregnancy and neuropsychological functioning (Poels et al 2022 ).…”
Section: Discussionsupporting
confidence: 92%
“…A high number of generated words reflects good functioning. A detailed description of the selected subtests may be found in our previously published paper 21 . Presence of learning problems and/or psychiatric disorders was assessed by parental report, worded as follows: “Has your child been diagnosed with a psychiatric disorder?…”
Section: Methodsmentioning
confidence: 99%
“…The current investigation was part of a cohort study designed to investigate neurodevelopmental functioning of children of mothers with SMI who were exposed or unexposed to lithium or antipsychotic medication in utero. 21 Patients were recruited from three centers in the…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…However, both studies had a retrospective design and a small cohort [ 24 , 53 ]. The prospective studies of Schou (1976) and Jacobson et al (1992) reported no differences in development between exposed children and controls [ 9 , 54 , 55 ], and very recently Poels et al (2022) found no evidence for significantly altered neuropsychological functioning of children (6–14 years) with previously in utero exposure to lithium [ 56 ]. Third, the data were retrospectively collected, which means they were dependent on the quality of the registration of data in medical records.…”
Section: Discussionmentioning
confidence: 99%